Quality Requirements for Barley - Shermakhmatovich, Sarmanov Sherzod; Khotamovich, Choriev Uktam (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
Lack of quality (beer, pearl barley and other food) varieties of barley. Use of samples from the world collection, selection of local varieties and samples from world collections, and selection of primary sources.